1984
DOI: 10.1007/bf00232359
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation for acute leukemia using transplant chemopurified with metabolite of oxazaphosphorines (ASTA Z 7557, INN mafosfamide)

Abstract: The contamination of autologous marrow with clonogenic tumor cells has been the main argument against ABMT in acute leukemia. In a preclinical study we evaluated an active cyclophosphamide derivative named "ASTA Z 7557". We observed that the toxic effect of this drug on CFU-GM growth was dependent on nucleated cell concentration as well as on red blood cell contamination. The potency of the drug was in close relationship with the incubation temperature. The growth of leukemic CFU was inhibited with an ASTA Z d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For PBPC, reports of relapse after PBPCT suggest that mobilized leukemic progenitor cells can contribute to relapse in a similar way to bone marrow. 13,14 Several groups have demonstrated the clinical feasibility of mafosfamide-purged ABMT with good clinical results. 13,15,16 Gorin 2,3 and Laporte et al 17 have shown in a series of 125 patients receiving mafosfamide-purged autografts that high CD34 + counts before purging correlates with a low transplant-related mortality and aggressive purging correlates with a low risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For PBPC, reports of relapse after PBPCT suggest that mobilized leukemic progenitor cells can contribute to relapse in a similar way to bone marrow. 13,14 Several groups have demonstrated the clinical feasibility of mafosfamide-purged ABMT with good clinical results. 13,15,16 Gorin 2,3 and Laporte et al 17 have shown in a series of 125 patients receiving mafosfamide-purged autografts that high CD34 + counts before purging correlates with a low transplant-related mortality and aggressive purging correlates with a low risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Several groups have demonstrated the clinical feasibility of mafosfamide-purged ABMT with good clinical results. 13,15,16 Gorin 2,3 and Laporte et al 17 have shown in a series of 125 patients receiving mafosfamide-purged autografts that high CD34 + counts before purging correlates with a low transplant-related mortality and aggressive purging correlates with a low risk of relapse. It was further shown that the best results in vivo are achieved when the number of CD34 + cells in the graft is very high and the graft is then purged as aggressively as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In its present form mafosfamide is of little clinical interest for iv administration but may be useful for treating harvested bone marrow in an attempt to purge it of tumor cells (5). It may also be of use for regional or topical therapies.…”
Section: Discussionmentioning
confidence: 99%
“…These studies clearly established that tumor cells may be eliminated from normal marrow suspensions without completely destroying the pluripotent stem cells. Several teams throughout the world, in the United States [31], France [32], including our team in Paris [33][34][35][36], Germany [37] and Italy started programs of ABMT with high dose cyclophosphamide and TBI (single dose at 10 Gy or fractionated at 12 Gy) using marrow purged in vitro with either 4HC in the United States, or mafosfamide (a related compound) in Europe. Most teams treated the marrow with fixed doses of mafosfamide while we adjusted the dose to what we considered to be the maximum tolerated dose defined as sparing 5% residual CFU-GM [33,35,36].…”
Section: Autologous Bone Marrow Transplantation With Purged and Unpurged Marrowmentioning
confidence: 99%